Pancasila sebagai Landasan Etika dan Karakter dalam Pengembangan Pariwisata Indonesia - Agnia Nagita Selvira; Al Nur Andari; Firda Rahma Solihah; Syifa Putri Gunawan; Supriyono Supriyono (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2026)
This study aims to identify and analyze the application of Pancasila values in the development of Indonesian tourism as a foundation for ethics and character. The method used is library research, reviewing various relevant written sources, including books, journals, articles, and other academic publications. The findings indicate that globalization exerts both positive and negative influences on Indonesian tourism, while simultaneously opening opportunities for the advancement of more ethical and responsible tourism practices. The integration of Pancasila values within the tourism sector such as mutual cooperation, environmental stewardship, social justice, and respect for cultural diversity can foster sustainable tourism development that balances economic growth with moral responsibility. Furthermore, these values contribute to strengthening national identity, preserving local wisdom, and enhancing community participation in tourism activities. The study also highlights that tourism grounded in Pancasila principles can improve social welfare by empowering local communities and promoting inclusive development. In conclusion, the application of Pancasila principles in tourism development is essential for maintaining a balance between economic progress and socio-cultural preservation, while reinforcing national character and resilience in the face of globalization and rapid global change.